Cost Analysis for a Small-Scale Hybrid, Hydrogen-Based PV Energy System - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 41st European Photovoltaic Solar Energy Conference)

Dimensioning and Lifetime Prediction Model for a Hybrid, Hydrogen-Based Household PV Energy System Using Matlab/Simulink - Möller, Marius Claus; Krauter, Stefan (Solar)
This paper presents a model of an energy system for a private household extended by a lifetime prognosis. The energy system was designed for fully covering the year-round energy demand of a private household on the basis of electricity generated by a photovoltaic (PV) system, using a hybrid energy storage system consisting of a hydrogen unit and a lithium-ion battery. Hydrogen is produced with a Proton Exchange Membrane (PEM) electrolyser by PV surplus during the summer months and then stored in a hydrogen tank. Mainly during winter, in terms of lack of PV energy, the hydrogen is converted back into electricity and heat by a fuel cell. The model was created in Matlab/Simulink and is based on real input data. Heat demand was also taken into account and is covered by a heat pump. The simulation period is a full year to account for the seasonality of energy production and demand. Due to high initial costs, the longevity of such an energy system is of vital interest. Therefore, this model was extended by a lifetime prediction in order to optimize the dimensioning with the aim of lifetime extension of a hydrogen-based energy system. Lifetime influencing factors were identified on the basis of a literature review and were integrated in the model. An extensive parameter study was performed to evaluate different dimensionings regarding the energy balance and the lifetime of the three components, electrolyser, fuel cell and lithium-ion battery. The results demonstrate the benefits of a holistic modelling approach and enable a design optimization regarding the use of resources, lifetime and self-sufficiency of the system

Evaluation of the Influence of Different Energy Usage Behavior, Component Dimensionings and PV Orientations on the Suitability and Lifetime of a Hybrid, Hydrogen-Based PV Energy System for a Private Household - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 40th European Photovoltaik Solar Energy Conference and Exhibition)

Investigation of Different Load Characteristics, Component Dimensioning, and System Scaling for the Optimized Design of a Hybrid Hydrogen-Based PV Energy System - Möller, Marius Claus; Krauter, Stefan (Hydrogen)
The realization of a carbon-neutral civilization, which has been set as a goal for the coming decades, goes directly hand-in-hand with the need for an energy system based on renewable energies (REs). Due to the strong weather-related, daily, and seasonal fluctuations in supply of REs, suitable energy storage devices must be included for such energy systems. For this purpose, an energy system model featuring hybrid energy storage consisting of a hydrogen unit (for long-term storage) and a lithium-ion storage device (for short-term storage) was developed. With a proper design, such a system can ensure a year-round energy supply by using electricity generated by photovoltaics (PVs). In the energy system that was investigated, hydrogen (H2) was produced by using an electrolyser (ELY) with a PV surplus during the summer months and then stored in an H2 tank. During the winter, due to the lack of PV power, the H2 is converted back into electricity and heat by a fuel cell (FC). While the components of such a system are expensive, a resource- and cost-efficient layout is important. For this purpose, a Matlab/Simulink model that enabled an energy balance analysis and a component lifetime forecast was developed. With this model, the results of extensive parameter studies allowed an optimized system layout to be created for specific applications. The parameter studies covered different focal points. Several ELY and FC layouts, different load characteristics, different system scales, different weather conditions, and different load levels—especially in winter with variations in heating demand—were investigated.

Microinverter testing update using high power modules: Efficiency, yield, and conformity to a new ”estimation formula” for variation of PV panel size - Krauter, Stefan; Bendfeld, Jörg; Möller, Marius Claus (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
The market for microinverters is growing, especially in Europe. Driven by the strongly rising prices for electricity, many small photovoltaic energy systems are being installed. Since monitoring for these plants is often quite costly, their yields are often not logged. Since 2014, microinverters have been studied at the University of Paderborn. The investigations are divided into indoor and outdoor tests. In the indoor area conversion efficiencies as a function of load have been measured with high accuracy and ranked according to Euro- and CEC weightings. In the outdoor laboratory, the behavior in the real world is tested. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules. Here, the investigations were carried out with modules of the power of 215 Wp until the year 2020. Because of the increasing module power nowadays, modules with an output of 360 Wp are now being used. To assess the influence of PV module size, two extremes have been investigated: A rather small module with 215 Wp - as it has been used 10 years ago, and a brand-new module (2021) offering 360 Wp. Both types of modules contain 60 solar cells in series connection. Appling the low-power modules, the challenge for the different micro-inverters has been during weak-light conditions, using the high-power modules, some inverters temporarily reach their power limits and yield is reduced. A method using a reference configuration of inverter & module and a linear equation resulting in the actual yield, any module & inverter configuration can be characterized by just the two coefficients.

Model of a Self-Sufficient PV Home using a Hybrid Storage System based on Li-Ion Batteries and Hydrogen Storage with Waste Heat Utilization - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
This paper provides a hybrid energy system model created in Matlab/Simulink which is based on photovoltaics as its main energy source. The model includes a hybrid energy storage which consists of a short-term lithium-ion battery and hydrogen as long-term storage to ensure autonomy even during periods of low PV production (e.g., in winter). The sectors heat and electricity are coupled by using the waste-heat generated by production and reconversion of hydrogen through an electrolyser respectively a fuel cell. A heat pump has been considered to cover the residual heat demand (for well insulated homes). Within this paper a model of the space heating system as well as the hot water heating system is presented. The model is designed for the simulation and analysis of a whole year energy flow by using a time series of loads, weather and heat profiles as input. Moreover, results of the energy balance within the energy system by simulation of a complete year by varying the orientation (elevation and azimuth) of the PV system and the component sizing, such as the lithium-ion battery capacity, are presented. It turned out that a high amount of heating energy can be saved by using the waste heat generated by the electrolyser and the fuel cell. The model is well suited for the analysis of the effects of different component dimensionings in a hydrogen-based energy system via the overall energy balance within the residential sector.

Hybrid Energy System Model in Matlab/Simulink based on Solar Energy, Lithium-Ion Battery and Hydrogen - Möller, Marius Claus; Krauter, Stefan (Energies / Special Issue "Sustainable Energy Concepts for Energy Transition")
In this paper, a model of a hybrid, hydrogen-based energy system for a household which includes the heating sector is presended. With such an energy system it's possible to enable energy autarky over a whole year based on solar energy. The scope of this study was to present a verified hybrid energy system model created in Simulink which can be used to prospectively size future similar energy systems where hydrogen in combination with a li-ion battery shall be used as energy storage type.